2022
DOI: 10.3390/ma15041426
|View full text |Cite
|
Sign up to set email alerts
|

Finite Boundary Conditions Due to the Bar Presence in the Model of Chloride Penetration

Abstract: The chloride penetration is usually modelled through the application of a solution of Fick’s second law of diffusion, based on the assumption of semi-infinite boundary conditions. However, the presence of the bars, on whose surface the chlorides accumulate, makes this assumption incorrect. As the time progresses, the chlorides in the steel/concrete interface increase in concentration more than the chlorides overpassing the bar position without obstacles. This circumstance, although previously studied, has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Tavares and Andrade [ 7 ] demonstrated that the usual modelling of chloride penetration, based on Fick’s second law of diffusion, is significantly affected by the presence of reinforcements. In this case, the assumption of semi-infinite boundary conditions is no longer valid, and the chloride concentration at the reinforcement depth becomes higher than that estimated from Fick’s second law.…”
mentioning
confidence: 99%
“…Tavares and Andrade [ 7 ] demonstrated that the usual modelling of chloride penetration, based on Fick’s second law of diffusion, is significantly affected by the presence of reinforcements. In this case, the assumption of semi-infinite boundary conditions is no longer valid, and the chloride concentration at the reinforcement depth becomes higher than that estimated from Fick’s second law.…”
mentioning
confidence: 99%